Molecular insights and clinical implications of DNA methylation in sepsis-associated acute kidney injury: a narrative review - Lili Liu; Saisai Ni; Lianna Zhang; Yingying Chen; Mengqi Xie; Xiaojing Huang (BMC Nephrology)
Abstract Sepsis-induced acute kidney injury (S-AKI) is a life-threatening complication of sepsis, marked by dysregulated inflammation, metabolic derangements, and immune dysfunction, driving high mortality. Its multifactorial pathogenesis increasingly implicates DNA methylation-a core epigenetic mechanism-as a critical disease modulator. This review synthesizes current knowledge of DNA methylation in S-AKI, covering molecular mechanisms, cellular dysfunction, and translational potential. In immune cells, sepsis-induced aberrant DNA methylation promotes hypomethylation of pro-inflammatory genes and hypermethylation of anti-inflammatory loci, exacerbating cytokine storms and immunosuppression. In renal tubular epithelial cells, abnormal methylation disrupts apoptosis, oxidative stress responses, and mitochondrial bioenergetics, impairing repair and accelerating S-AKI progression. Renal vascular endothelial cells exhibit methylation-dependent dysregulation of vasoactive and inflammatory pathways, compromising microvascular homeostasis and renal hemodynamics. DNA methylation signatures offer promise as early S-AKI biomarkers, with cell-type-specific patterns reflecting severity, injury, and prognosis. Targeting DNA methyltransferases with epigenetic modifiers represents a novel therapy, though challenges arise from sepsis’s complex epigenetic landscape-bidirectional methylation changes, histone crosstalk, and context-dependent responses. A key paradox lies in DNA methylation’s dual traits: stability underpinning biomarker reliability and plasticity enabling dynamic inflammatory adaptation, yet introducing therapeutic heterogeneity. Future research should prioritize dissecting cell-specific methylation mechanisms, integrating multi-omics to identify epigenetic subnetworks, and developing real-time monitoring tools for precision diagnosis and tailored interventions. Advancing these frontiers may translate epigenetic insights into transformative strategies to improve outcomes for this devastating condition.